Newton, we have a problem... - Yeo, Shelley; Zadnik, Marjan (Australian Science Teachers' Association, 2000)
Many Year 12 physics students in Western Australia have inadequate and underdeveloped conceptions about force, preventing them from reasoning effectively about situations involving forces. They are unable to consistently and accurately represent forces in diagrams because they cannot identify the forces acting in any given situation. While part of their difficulty may be attributed to naive conceptions learned through experience, teachers and scientists may be inadvertently contributing to the maintenance of students' alternative conceptions through their representations of physics. Newton, himself, may be at the heart of the problem. Constructivism, which describes how people know and learn, encompasses the assertion that children's learning is dependent on what they already know. Children enter high school with many Aristotelian conceptions of force and motion, and this knowledge determines how they subsequently internalise and remember further information. If we are to help students make more productive sense of physics we must examine how our teaching and portrayal of physics reinforces these naive force-motion conceptions and then design more effective teaching/learning strategies.